(untitled) (Journal of Oriental Studies, 2016)
The article attempts to plot and thematic classifi cation of historical novels J.Zeydan. Of the nineteen historical novels J.Zeydan two novels were devoted to events in the late XYIII century and the fi rst half of XIX century, and the remaining seventeen novels refl ect the events of the Middle Ages reproduced in chronological order cycles.